Supply Chain Performance Measurement and Improvement for Sugarcane Agro-industry - Muhammad Asrol; Marimin Marimin; Machfud Machfud (International Journal of Supply Chain Management, 2017)
The supply chain performance is an indicator of success company in conducting the business process. The measurement of supply chain performance is required to take control and recognize the companys performance position. The objectives of this research were to identify business process value-added within the supply chain, to measure the supply chain performance, and to formulate strategies for improving the supply chain performance. The value-added identification was conducted by Hayami method. The supply chain performance was measure by Supply Chain Operation Reference (SCOR) combine with fuzzy Analytic Hierarchy Process (AHP). Strategies for supply chain performance improvement were formulated through of SWOT analyses combine with fuzzy-AHP. The value-added analysis result showed that the sugarcane factory was the highest value added ratio in the supply chain. The supply chain performance measurement result showed that the sugarcane factory has poor performance while plantation was in very low performance. Evaluation of supply chains internal and external factors through SWOT indicated a strong condition and would deal with possibly great threats. Based on Fuzzy AHP, this study suggests research encouragement and development in the sugar production system in order to maintain qualities, yields and performance to improve supply chain performance eventually.